2019
DOI: 10.1124/jpet.119.258566
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenergic Mechanisms in Fentanyl-Mediated Rapid Death Explain Failure of Naloxone in the Opioid Crisis

Abstract: In December 2018, the Centers for Disease Control declared fentanyl the deadliest drug in America. Opioid overdose is the single greatest cause of death in the United States adult population (ages 18-50), and fentanyl and its analogs [fentanyl/ fentanyl analogs (F/FAs)] are currently involved in .50% of these deaths. Anesthesiologists in the United States were introduced to fentanyl in the early 1970s when it revolutionized surgical anesthesia by combining profound analgesia with hemodynamic stability. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
130
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(134 citation statements)
references
References 185 publications
(466 reference statements)
4
130
0
Order By: Relevance
“…Fentanyl is 50-100 times more potent than morphine (Suzuki and El-Haddad, 2017), and causes respiratory depression, chest wall rigidity, and loss of consciousness which can rapidly lead to hypoxia, hypercarbia, and death if not treated promptly (Henderson et al, 2014;Lalley et al, 2014;Torralva and Janowsky, 2019). Fentanyl is commonly administered as a potent analgesic in a variety of formulations, including intravenous, transdermal, and sublingual.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fentanyl is 50-100 times more potent than morphine (Suzuki and El-Haddad, 2017), and causes respiratory depression, chest wall rigidity, and loss of consciousness which can rapidly lead to hypoxia, hypercarbia, and death if not treated promptly (Henderson et al, 2014;Lalley et al, 2014;Torralva and Janowsky, 2019). Fentanyl is commonly administered as a potent analgesic in a variety of formulations, including intravenous, transdermal, and sublingual.…”
Section: Introductionmentioning
confidence: 99%
“…Although intravenous fentanyl administration is generally safe in the perioperative setting with appropriate monitoring, opioidinduced respiratory depression is still a common postoperative complication that can affect up to 17% of patients (Cashman and Dolin, 2004). In addition, fentanyl causes approximately 60,000 drug overdose deaths each year in the United States, making it a significant public health problem (Scholl et al, 2018;Torralva and Janowsky, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Opioid-induced chest wall rigidity, also called "WoodenChest Syndrome (WCS)", has been known for decades, although it is usually described in the anesthesiology literature related to surgical procedures [8] [36]. WCS presents as musclewall rigidity, laryngospasm, seizure-like events, cyanosis, and loss of consciousness [37] [38].…”
Section: The Complication Of Naloxone Vs Fentanyl and Fentanoidsmentioning
confidence: 99%
“…This has been used as support for the argument that WCS is a cause of fentanoid-induced respiratory depression and overdose death. Not only is WCS not reversed by an ORA-an ORA may make it worse [36]. It has been suggested that fentanoid overdose sets up a potential "double-whammy": WCS and respiratory depression [22].…”
Section: The Complication Of Naloxone Vs Fentanyl and Fentanoidsmentioning
confidence: 99%
See 1 more Smart Citation